Anxiety levels of university hospital nurses during the Covid‐19 pandemic. Issue 4 (13th January 2021) - Yurtseven, Şeyma; Arslan, Sevban
Abstract: Purpose: The aim of this study was to determine the anxiety levels of nurses caused by the changes experienced during the Covid‐19 pandemic. Design and Methods: The sample of the study consisted of 270 nurses. The data were collected using a questionnaire and the State Anxiety Inventory. The data were analyzed using descriptive statistics, t test, analysis of variance, Kruskal–Wallis and Tukey's test. Findings: It was found that of the total number of nurses, 85.6% had high anxiety levels. Practical Implications: Early intervention of indirect traumatization might facilitate controlling anxiety resulting from the Covid‐19 outbreak. Conducting further supportive administrative studies to reduce anxiety levels is recommended.